Latrodectus geometricus (Aranea: Theridiidae) envenoming: Rapid resolution of symptoms following F(ab')2 antivenom therapy. (December 2020) - Keyler, D.E.; Ahmad, M.; Rodriguez, A.; De Silva, P.M.K.
Abstract: The Brown Widow spider ( Latrodectus geometricus ) is an invasive species whose geographic range has been expanding worldwide. It is a relative species of the Black Widow and Red-backed spiders of the genus Latrodectus . Despite its broad geographic distribution cases of Brown Widow envenomation have rarely been documented. The venom of L. geometricus is similar to the venom of L. mactans with the primary venom component being alpha-latrotoxin, and consequent envenoming by L. geometricus to humans has resulted in symptoms similar to those reported for other Latrodectus spp. Specific FDA approved Latrodectus antivenom (IgG) available in North America has been effectively used in treating venom-induced symptoms following L. mactans envenoming. The patient reported here involved a confirmed L. geometricus envenoming who was efficaciously treated with an alternately available F(ab')2 antivenom from Mexico. Highlights: Brown Widow geographic range is spreading in the USA, yet envenoming reports are rare. Latrodectus geometricus is a medically important invasive spider species in the USA. Rapid and profound pain developed following L. geometricus envenoming. Latrodectus species antivenom, Acramyn Plus®, rapidly resolved envenoming symptoms.